Investigation of growth, development, and factors associated with injury in elite schoolboy footballers: prospective study. (26th February 2009) - Johnson, Amanda; Doherty, Patrick Joseph; Freemont, Anthony
Abstract : Objective To investigate the differences between skeletal and chronological age and to assess the role of maturity status, anthropometric data, and football related variables in explaining injury statistics in elite schoolboy footballers. Design Prospective study of injuries in schoolboy footballers according to skeletal age. Setting Premier league football club in England. Participants 292 schoolboy players (age 9-16) registered at the club Interventions Annual x ray film of hand or wrist. Main outcome measures Data on injury 2001-7. Skeletal age determined with the Fels method. Skeletal age of more than one year above chronological age was classified as an early maturer, within one year as a normal maturer, and more than one year below normal as a late maturer. Injury and hours of training and rates of exposure to match play. Results Over six years 476 injuries were reported. The mean chronological age (11.74 (SD 2.35) years) and skeletal age defined by x ray picture (12.08 (SD 3.14) years) showed a significant mean difference of −0.344 (95% confidence interval −0.490 to −0.198; t =−4.64, df=280). Analysis of covariance showed that injury incidents did not differ significantly with maturity status after adjusting for training time, playing time, height, and position played ( F =0.32, 160, P=0.73). General log linear analysis with a Poisson model showed that difference in maturity, playing hours, and training hours collectively explained 48% of the variance in injury incidents. Injury exposure rates differed considerably, with 1.44/1000 hours for training and 10.5/1000 hours for match play. Conclusion Maturity, defined by the difference between chronological age and skeletal age, plus training and playing hours together predict injury in schoolboy footballers. Injury exposure rates were higher for match play than training, which could have implications for targeting preventative interventions by academy staff. The use of skeletal age measurements to establish accurate "windows of opportunity" for training is more appropriate than the commonly used chronological age. Caution is needed when interpreting differences in injury occurrence as the factors that contribute are often complex.